Towards a new hinterland orientation for the port of Rotterdam: the entrepreneurial port - Arjen Van Klink; Willem van Winden (European Regional Science Association (ERSA), 1998)
Fundamental changes set a new scene for seaports. In the new situation, ports can no longer rely only on infrastructure and transport services to optimise their hinterland reach. To optimise inland accessibility, port authorities have to look beyond infrastructure and give more value to intangible aspects of accessibility. It is recommended to exploit and combine the knowledge available in the port community, by developing innovative logistic concepts to bind shippers and regions to the port. Such a new hinterland approach is especially relevant for the port of Rotterdam. Rotterdam seems to have difficulties to penetrate in regions outside its captive market: the share of rail transport still is relatively low and its presence in Central Europe falls short to its ?mainport? status. To secure its present market and to extend its market reach towards Central Europe, a more active orientation on the shipper is required as a complement to infrastructure investments. The recently developed transport concept for Chrysler can be considered as an illustration of a new hinterland approach.
Keywords: 330